CELAH-CELAH PENURUNAN SUKU BUNGA PINJAMAN DALAM RANGKA MEMBERDAYAKAN UMKM - I Wayan Wardita; Ni Made Gunastri (Forum Manajemen, 2012)
Globalization in the ï¬ eld of industry cannot be avoided along withthe development of telecommunication. By the development of communicationstechnology, the business competitions are more competitive. Therefore, the cellularoperators compete to provide excellent service by offering a wide range of productvariants all of which focused on increasing customer satisfaction. The increasing ofcustomer satisfaction will result in the increase of customer loyalty. And that is alsoimplemented by Telkomsel (Kartu Halo), one of the cellular operators. The KartuHalo outlet in Tabanan optimizes their various facilities and services to enhancecustomer satisfaction. However, customer complaints always arise and result in thedeclining number of costumer who activated the card in Kartu Halo Outlet in Tabanan. From that point we will questioning, is there any inï¬‚ uence of customer satisfaction on customer loyalty. The results of the study show that customer satisfaction has asigniï¬ cant effect on customer loyalty. So it is suggested to the company managementto constantly improve customer satisfaction through the improvement of qualityservice, which in turn is expected to increase customer loyalty.